2013
DOI: 10.3892/or.2013.2825
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib alters the malignant phenotype of osteosarcoma cells via downregulation of the activity of the HER2-PI3K/AKT-FASN axis in vitro

Abstract: Lapatinib, an inhibitor of human epidermal growth factor receptor 2 (HER2) phosphorylation, has been reported to inhibit several types of tumors such as HER2-overexpressing breast cancer. However, the effect of lapatinib on the malignant phenotype of human osteosarcoma (OS) cells and the potential molecular mechanisms remain unclear. To elucidate the effect of lapatinib on OS, two OS cell lines, U2-OS and MG-63, were utilized in the present study. Various concentrations of lapatinib were used to treat OS cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…accumulating evidence has indicated an important role of the Pi3K/aKT signaling pathway in osteosarcoma (11,34,35); Pi3K/aKT signaling modulates the proliferation, invasion, migration and apoptosis of osteosarcoma cell lines (36)(37)(38)(39)60). Previous studies revealed that alantolactone is a specific inhibitor in several diseases via the Pi3K/aKT signaling pathway (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…accumulating evidence has indicated an important role of the Pi3K/aKT signaling pathway in osteosarcoma (11,34,35); Pi3K/aKT signaling modulates the proliferation, invasion, migration and apoptosis of osteosarcoma cell lines (36)(37)(38)(39)60). Previous studies revealed that alantolactone is a specific inhibitor in several diseases via the Pi3K/aKT signaling pathway (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the Pi3K/aKT signaling pathway serves an important role in osteosarcoma (11,34,35); Pi3K/aKT modulates the proliferation, invasion, migration and apoptosis of osteosarcoma cell lines (36)(37)(38)(39). Thus, the effect of alT on the Pi3K/aKT signaling pathway was investigated to confirm whether it is the mechanism by which ALT affects osteosarcoma cells.…”
Section: Inhibitory Mechanisms Of Alt In Osteosarcoma Cellsmentioning
confidence: 99%
“…The FASN inhibitor C75 can repress the expression of FASN, ErbB1, ErbB2 and Akt, suggesting that FASN may participate in the ErbB/Akt pathway (24). The ErbB2 inhibitor lapatinib is able to suppress the activity of the ErbB2/PI3K/Akt/FASN pathway (25). Dysregulation of the PI3K/Akt pathway has been shown to have an association with autism (26); therefore, it is speculated that alterations of the ErbB2/PI3K/Akt/FASN signaling pathway may be involved in autism.…”
Section: Discussionmentioning
confidence: 99%
“…In human osteosarcoma, Lapatinib alters the malignant phenotype of cells via downregulation of the activity of the ErbB2-PI3K/AKT-FASN axis in vitro (103). A phase II trial on Lapatinib showed a modest antitumor activity in ErbB1-positive advance chordoma patients.…”
Section: Lapatinibmentioning
confidence: 98%